2021
DOI: 10.3389/fmicb.2021.661382
|View full text |Cite
|
Sign up to set email alerts
|

Development and Application of a Fast Method to Acquire the Accurate Whole-Genome Sequences of Human Adenoviruses

Abstract: The whole-genome sequencing (WGS) of human adenoviruses (HAdVs) plays an important role in identifying, typing, and mutation analysis of HAdVs. Nowadays, three generations of sequencing have been developed. The accuracy of first-generation sequencing is up to 99.99%, whereas this technology relies on PCR and is time consuming; the next-generation sequencing (NGS) is expensive and not cost effective for determining a few special samples; and the third-generation sequencing technology has a higher error rate. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 52 publications
1
2
0
Order By: Relevance
“…In the age group, 51+ years was also 3 (2.9%) using the IgM ELIZA test. These results were consistent with the results reported by Zhao et al (2021), 12 that HAdV ranges between 5 to 15% of patients with upper and lower hospitalized RTIs. Our study was consistent with previous studies that found that HAdV has a significant role in pediatric upper and lower RTIs, as its frequency range between 2 to 5% of the overall upper and lower RTIs and 4 to 10% of pneumonia, particularly in pediatric and immune-compromised patients.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In the age group, 51+ years was also 3 (2.9%) using the IgM ELIZA test. These results were consistent with the results reported by Zhao et al (2021), 12 that HAdV ranges between 5 to 15% of patients with upper and lower hospitalized RTIs. Our study was consistent with previous studies that found that HAdV has a significant role in pediatric upper and lower RTIs, as its frequency range between 2 to 5% of the overall upper and lower RTIs and 4 to 10% of pneumonia, particularly in pediatric and immune-compromised patients.…”
Section: Discussionsupporting
confidence: 93%
“…2 Furthermore, some severe upper and lower RTIs duo to adenovirus may develop chronic difficulties, e.g., bronchiolitis obliterans and bronchiectasis cases. 12 The current study showed that 1(12.5%) was positive for HAdV using IgG ELIZA in 8 upper respiratory tract infected patients. Of 66 patients with pneumonia, 5(7.6%) were positive for HAdV using IgG ELIZA.…”
Section: Discussionmentioning
confidence: 48%
“…First, a novel adenovirus GZ3-12 was isolated from a fecal sample of a rhesus macaque as noted earlier; this was subsequently amplified in HEK293 cells. Viral genomic DNA was extracted from GZ3-12 using the modified extraction method described earlier by us ( 55 ). Separately, pBR322 was digested by Eco RI, with the linearized product serving as the PCR template.…”
Section: Methodsmentioning
confidence: 99%